The logic of experimental tests, particularly of Everettian quantum theory. (August 2016) - Deutsch, David
Abstract: Claims that the standard procedure for testing scientific theories is inapplicable to Everettian quantum theory, and hence that the theory is untestable, are due to misconceptions about probability and about the logic of experimental testing. Refuting those claims by correcting those misconceptions leads to an improved theory of scientific methodology (based on Popper׳s) and testing, which allows various simplifications, notably the elimination of everything probabilistic from the methodology ('Bayesian' credences) and from fundamental physics (stochastic processes). Highlights: Everettian quantum theory is testable. Stochastic theories suffer from a flaw in the logic of their testability. Popper׳s methodology is needed to understand the testability of quantum theory.